2014
DOI: 10.1016/j.dld.2013.07.020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of opiate pain medications and psychoactive drugs on the quality of colon preparation in outpatient colonoscopy

Abstract: Background Suboptimal colon preparation is a significant barrier to quality colonoscopy. The impact of pharmacologic agents associated with gastrointestinal dysmotility on quality of colon preparation has not been well characterized. Aims Evaluate impact of opiate pain medication and psychoactive medications on colon preparation quality in outpatient undergoing colonoscopy. Methods Outpatients undergoing colonoscopy at a single medical center during a 6-month period were retrospectively identified. Demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
4
6
0
Order By: Relevance
“…This study supports the results of previous studies showing the negative impact of opioid use on bowel preparation but also indicates that opioid use may be associated with more procedure‐related complications and slightly longer procedure times. These differences were generally relatively small.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This study supports the results of previous studies showing the negative impact of opioid use on bowel preparation but also indicates that opioid use may be associated with more procedure‐related complications and slightly longer procedure times. These differences were generally relatively small.…”
Section: Discussionsupporting
confidence: 90%
“…Findings from previous studies support the association of opioid exposure and male gender with poor bowel preparation quality . In addition, the proportion of patients who were unexposed to opioids with adequate bowel preparation was comparable in this study (87.3%) with that reported in previous studies (75.6% and 90.7%) . In the current study, the use of opioids was also shown to have an impact on other colonoscopy outcomes, beyond the adequacy of bowel preparation.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations